Rumsfeld's rules leadership lessons in business,politics, war and life - Rumsfeld, Donald (Broadside Books, 2013)
Throughout his long and distinguished career?as a naval aviator, a U.S. Congressman, a top aide to four American presidents, a high-level diplomat, a CEO of two Fortune 500 companies, and the only twice-serving Secretary of Defense in American history?Donald Rumsfeld has collected hundreds of pithy, compelling, and often humorous observations about leadership, business, and life. When President Gerald Ford ordered these aphorisms distributed to his White House staff in 1974, the collection became known as "Rumsfeld's Rules."
Includes bibliographical references (pages 333-334) and index.
Keywords: Rumsfeld, Donald, 1932-